Financial Ratio Analysis: An Assessment Of Malaysian Contracting Firms - Halim, Mohd Suberi Ab.; Jaafar, Mastura; Osman, Omar; Haniff, Md. Shariff (Penerbit Universiti Sains Malaysia, 2012)
This paper examines the role of financial management in the success or failure of construction firms. According to previous studies on the impact of financial factors in the failure of construction projects, poor financial management and lack of capital are the main determinants of construction failure. Failures in the construction industry are experienced not only by developing countries but also worldwide, and the failure scenario is present in the construction industry in Malaysia. The failure rate of construction companies in Malaysia is high. According to the Construction Industry Development Board Malaysia (CIDB), from January 2006 to August 2008, 11,321 construction companies were classified as dormant and non-active. There are very few successful contractors in Malaysia, and most construction projects cannot be completed within the original schedule. The sources of failure are directly related to financial factors. In this case study, 17 financial ratios were used to measure companies' financial performance. Six medium and large Bumiputera contractors were selected as case studies. This study found that most Bumiputera construction companies had insufficient cash capital to finance their construction work, experienced a low profit margin from construction projects and were highly dependent on debt capital to finance their construction costs. There was a lack of monitoring systems for cash flow and project costs. Without effective financial practices, construction companies are setting themselves up for failure.